The Impact Of International Trade On Human Resource Development In Indonesia - Riski Eko Ardianto; Rahmat Hidayat (Politeknik APP Jakarta, 2025)
This study aims to analyze the impact of international trade on human resource development (HRD) in Indonesia by focusing on the variables of international trade (X1), trade openness (X2), HR quality (Y1), HR development (Y2), and the moderating variable of HR adaptability (Z). Data were collected from 200 respondents including business actors, workers, and stakeholders in the trade and HRD development sectors. The influence model between variables was tested using Smart PLS 3.0 to identify the relationship between international trade and trade openness on HR quality and development. The results of the study indicate that international trade (X1) and trade openness (X2) have a significant effect on the quality of human resources (Y1), but international trade does not affect human resource development (Y2). The variable of human resource adaptability (Z) is able to mediate These findings indicate that increasing international trade activities and trade openness policies can improve workforce competence through investment in education, training, and technology.